"What the Wood wants to do": Pragmatist Speculations on a Response-able Architectural Practice. Issue 1 (2nd January 2018) - Lefebvre, Pauline
Abstract : Departing from observations collected in an architecture firm, this essay investigates the way in which an architect expressed his concerns for what the material he intended to use "wants to do". Adopting a speculative and pragmatist perspective, I detect there a possibility of thinking about architects' responsibility as a moral exchange with beings involved in the design process. The text addresses two interpretations of that situation that could hinder the possibility of a more relational architectural practice. The first reduces the designer's formulation to a rhetorical means to expose his ability to take constraints into account. The second interprets it as the expression of the architects' moral obligation to respect the material's intrinsic nature. Two diverging notions of responsibility are at stake, which are here contrasted with a third one. Built on a materialist view on ethics, the ethological perspective allows the acknowledgement of what the material and the designer become capable of together.